Hybrid Flash-SPS of TiNiCu0.05Sn with reduced thermal conductivity - Gucci, Francesco; Saunders, Theo Graves; Srinivasan, Bhuvanesh; Cheviré, François; Ferluccio, Daniella A.; Bos, Jan-Willem G.; Reece, Michael J. (Elsevier, 2020)
TiNiCu0·05Sn was sintered using Spark Plasma Sintering (SPS) and a new derivative processing method, hybrid Flash-SPS (hFSPS). The high heating rate achieved (7700 °C/min) produced almost single-phase samples with high density. The sample sintered at 1040 °C showed a higher power factor and a lower thermal conductivity than the SPS sample, resulting in a higher ZT at 350 °C (0.44 vs 0.35).
Keywords: Half-heusler; Thermoelectric; Flash sintering; Thermal conductivity